Bamboo in North East India - Loushambam, R S; Singh, Nongmaithem Raju; Taloh, Aido; Mayanglambam, Shankar (Indian Journal of Hill Farming, 2018)
Eastern states of India harbours a high diversity of bamboo. The maximum concentration of species is found in the deciduous and semi evergreen regions of North-east and the tropical moist deciduous forests of North and South India. The North-eastern hilly States of India harbour nearly 90 species of bamboos, 41 of which are endemic to that region. The state–wise distribution of bamboos in India is not completely known. Conservation through community based approach and by developing Bambusetum. Strengthening inventories of bamboo genetic resources in the region. Developing appropriate bamboo based agroforestry system. The high potential can be improved by suitable scientific intervention and local capacity building, which will have great implications in improving the socio-economic status of the entire region.